Embolism resistance in petioles and leaflets of palms. (30th August 2019) - Emilio, Thaise; Lamarque, Laurent J; Torres-Ruiz, José M; King, Andrew; Charrier, Guillaume; Burlett, Régis; Conejero, Maria; Rudall, Paula J; Baker, William J; Delzon, Sylvain
Abstract: Background and aims: Hydraulic studies are currently biased towards conifers and dicotyledonous angiosperms; responses of arborescent monocots to increasing temperature and drought remain poorly known. This study aims to assess xylem resistance to drought-induced embolism in palms. Methods: We quantified embolism resistance via P 50 (xylem pressure inducing 50 % embolism or loss of hydraulic conductivity) in petioles and leaflets of six palm species differing in habitat and phylogenetic relatedness using three techniques: in vivo X-ray-based microcomputed tomography, the in situ flow centrifuge technique and the optical vulnerability method. Key results: Our results show that P 50 of petioles varies greatly in the palm family, from −2.2 ± 0.4 MPa in Dypsis baronii to −5.8 ± 0.3 MPa in Rhapis excelsa (mean ± s.e.). No difference or weak differences were found between petioles and leaf blades within species. Surprisingly, where differences occurred, leaflets were less vulnerable to embolism than petioles. Embolism resistance was not correlated with conduit size ( r = 0.37, P = 0.11). Conclusions: This study represents the first estimate of drought-induced xylem embolism in palms across biomes and provides the first step towards understanding hydraulic adaptations in long-lived arborescent monocots. It showed an almost 3-fold range of embolism resistance between palm species, as large as that reported in all angiosperms. We found little evidence for hydraulic segmentation between leaflets and petioles in palms, suggesting that when it happens, hydraulic segregation may lack a clear relationship with organ cost or replaceability.